THE ANALYSIS OF ILLUCOTIONARY SPEECH ACT OF LEEN ALKASSAB’S SPEECH ON HARVARD MEDICAL SCHOOL YOUTUBE CHANNEL - Hafsohtul Zakiyah; Sartika Dewi Harahap; Akhrif Yahsya (IICLS (Indonesian Institute for Corporate Learning and Studies), 2025)
This research aims to identify the types of illocutionary acts and the dominant illocutionary acts used in the speech. This study employs a qualitative descriptive method. Data were collected through transcription and analyzed using data collection, data condensation, data display, and conclusion drawing/verification. The data were classified into multiple categories based on the concepts outlined in John R. Searle's theory. Only one speech by Leen Alkassab, delivered at the graduation ceremony for ambassador doctors at Harvard Medical School in the United States, was used as the data source for this research. The findings indicate two illocutionary acts: assertive, and expressive. Assertive acts were the most dominant found in the speech, with 22 occurrences, most of which involved stating functions. Expressive acts were found in 13 cases, with the illocutionary functions of gratitude and thanks being the most common. Directive and commissive acts were the least frequent, while declarative acts were not found in the speech, as they require specific conditions for declarative utterance to occur.